(untitled) (Pedagogical Horizons, 2025)
The text highlights professional relationship building as a key competence in school development consulting. From a systemic and group dynamics perspective, it shows how relationships, communication and conscious work with group dynamics are essential factors for sustainable change. The focus is particularly on the interaction between school management and consultants, as well as reflection on roles, expectations and resistance. Relationships are understood not as a framework, but as an active element of design. The article argues that sustainable organisational learning does not result from rigidly working through the planned steps of a project architecture, but rather from process-oriented consulting that focuses on relationships, participation and flexible responses to specific events.